Reporte de estudios de farmacovigilancia de medicamentos antihipertensivos en bases de datos electrónicas 2000-2016 - Zavala Urtecho, Ewaldo Debray (2017)
The purpose of this report is to report bibliographic information in electronic databases (Scopus, PubMed / MEDLINE, Scielo) from 2000 to 2016 regarding pharmacovigilance and adverse reactions to antihypertensive drugs. Information was also collected from the VigiBase database for The main antihypertensive drugs. The studies and statistical data obtained in the databases were carried out using different search strategies including Medical Subject Heading (MeSH). The Scopus database presented the highest number of registrations related to pharmacovigilance (5115) and pharmacovigilance in antihypertensive drugs (74); in PubMed / MEDLINE there were also more publications related to adverse reactions to antihypertensive drugs (263) than to Pharmacovigilance of antihypertensives (12), the largest number of publications in pharmacovigilance was given in 2014 (Scopus and Scielo), and since 2009 PubMed / MEDLINE publications on pharmacovigilance have been increasing. The major adverse reactions to antihypertensive drugs were cough (captopril, enalapril, lisinopril), dizziness (losartan, valsartan, irbesartan, carvedilol), nausea (nitroprusside), bradycardia (atenolol, bisoprolol), fever (methyldopa) and peripheral edema (amlodipine) , among other. The lack of information regarding the pharmacovigilance of antihypertensive drugs suggests the detailed study of the safety profiles of drugs to improve the drug therapeutics guidelines and quality of life of the hypertensive population worldwide